High cholesterol intake remodels cholesterol turnover and energy homeostasis in Nile tilapia (Oreochromis niloticus) - Rui-Xin Li; Ling-Yun Chen; Samwel M. Limbu; Yu-Cheng Qian; Wen-Hao Zhou; Li-Qiao Chen; Yuan Luo; Fang Qiao; Mei-Ling Zhang; Zhen-Yu Du (Marine Life Science & Technology, 2023)
The roles of dietary cholesterol in fish physiology are currently contradictory. The issue reflects the limited studies on the metabolic consequences of cholesterol intake in fish. The present study investigated the metabolic responses to high cholesterol intake in Nile tilapia ( Oreochromis niloticus ), which were fed with four cholesterol-contained diets (0.8, 1.6, 2.4 and 3.2%) and a control diet for eight weeks. All fish-fed cholesterol diets showed increased body weight, but accumulated cholesterol (the peak level was in the 1.6% cholesterol group). Then, we selected 1.6% cholesterol and control diets for further analysis. The high cholesterol diet impaired liver function and reduced mitochondria number in fish. Furthermore, high cholesterol intake triggered protective adaptation via (1) inhibiting endogenous cholesterol synthesis, (2) elevating the expression of genes related to cholesterol esterification and efflux, and (3) promoting chenodeoxycholic acid synthesis and efflux. Accordingly, high cholesterol intake reshaped the fish gut microbiome by increasing the abundance of Lactobacillus spp. and Mycobacterium spp., both of which are involved in cholesterol and/or bile acids catabolism. Moreover, high cholesterol intake inhibited lipid catabolic activities through mitochondrial β-oxidation, and lysosome-mediated lipophagy, and depressed insulin signaling sensitivity. Protein catabolism was elevated as a compulsory response to maintain energy homeostasis. Therefore, although high cholesterol intake promoted growth, it led to metabolic disorders in fish. For the first time, this study provides evidence for the systemic metabolic response to high cholesterol intake in fish. This knowledge contributes to an understanding of the metabolic syndromes caused by high cholesterol intake or deposition in fish.